Analysis On The Influence Of Current Ratio, Debt to Equity Ratio and Total Asset Turnover Toward Return On Assets On The Otomotive and Component Company That Has Been Registered In Indonesia Stock Exchange Within 2011-2017 - Mimelientesa Irman; Astri Ayu Purwati (Yayasan Riset dan Pengembangan Intelektual, 2020)
A good company can be seen from the level of return on assets invested, and it affects the interest of an investor to invest in. But the high or low level of profit can be influenced by the financial performance of one of the financial performance is the Current Ratio, Debt to Equity Ratio, and Total Asset Turnover. Therefore, a study was conducted to find out whether the Current Ratio, Debt to Equity Ratio, and Total Asset Turnover had an effect on Return On Assets in Automotive and Component companies listed on the Indonesia Stock Exchange for the period 2011-2017. The study population consisted of 12 companies selected by purposive sampling. Financial report data is obtained from the Indonesia Stock Exchange (IDX). The data analysis technique used is multiple linear regression analysis with SPSS 19.0 and SMART PLS 2019 application tools. The results obtained from this study are the Current Ratio which has a significant effect on Return On Assets, Debt to Equity Ratio has a not significant negative effect on Return On Assets, and Total Asset has a significant positive effect on Return On Assets.